Modulatory Effects of Autophagy on APP Processing as a Potential Treatment Target for Alzheimer's Disease - Rahman, Md. Ataur; Rahman, Md Saidur; Rahman, MD. Hasanur; Rasheduzzaman, Mohammad; Mamun-Or-Rashid, A. N. M.; Uddin, Md Jamal; Rahman, Md Rezanur; Hwang, Hongik; Pang, Myung-Geol; Rhim, Hyewhon (MDPI AG, 2021)
Alzheimer's disease (AD) is characterized by the formation of intracellular aggregate composed of heavily phosphorylated tau protein and extracellular deposit of amyloid-beta (A beta) plaques derived from proteolysis cleavage of amyloid precursor protein (APP). Autophagy refers to the lysosomal-mediated degradation of cytoplasmic constituents, which plays a critical role in maintaining cellular homeostasis. Importantly, recent studies reported that dysregulation of autophagy is associated in the pathogenesis of AD, and therefore, autophagy modulation has gained attention as a promising approach to treat AD pathogenesis. In AD, both the maturation of autolysosomes and its retrograde transports have been obstructed, which causes the accumulation of autophagic vacuoles and eventually leads to degenerating and dystrophic neurites function. However, the mechanism of autophagy modulation in APP processing and its pathogenesis have not yet been fully elucidated in AD. In the early stage of AD, APP processing and A beta accumulation-mediated autophagy facilitate the removal of toxic protein aggregates via mTOR-dependent and -independent pathways. In addition, a number of autophagy-related genes (Atg) and APP are thought to influence the development of AD, providing a bidirectional link between autophagy and AD pathology. In this review, we summarized the current observations related to autophagy regulation and APP processing in AD, focusing on their modulation associated with the AD progression. Moreover, we emphasizes the application of small molecules and natural compounds to modulate autophagy for the removal and clearance of APP and A beta deposits in the pathological condition of AD.